Nanoindentation response of small-volume piezoelectric structures and multi-layered composites: modeling the effect of surrounding materials - Cheng, Guang; Wu, Zonglin; Venkatesh, T. A. (Frontiers in Electronic Materials, 2023)
With piezoelectric small-volume composites gaining importance in smart device applications and nanoindentation being recognized as a versatile method for assessing the properties of layer materials, the present study is focused on the indentation response of the small-volume piezoelectric structures multi-layered composites. In particular, the effects of the nature of the substrate and surrounding materials, on the indentation response of piezoelectric nanocomposites, such as nanoislands, nanowires, and multi-layered composites are investigated. By developing three-dimensional finite element modeling, the complex interaction between the fundamental elastic, piezoelectric and dielectric properties of the piezoelectric materials and the elastic, plastic and electrically conducting or insulating properties of the surrounding materials, on the indentation response of the layered composites is analyzed. It is found that: (i) the elastic and plastic properties of the underlying substrate materials have a profound influence on the indentation response of the piezoelectric structures. A a substrate material that is elastically stiffer enhances the mechanical indentation stiffness and the electric indentation stiffness while plastic deformation in the substrate causes a reduction in the mechanical and electrical indentation stiffness; (ii) the effective piezoelectric and mechanical indentation stiffnesses of piezoelectric multi-layered